1998
DOI: 10.1007/s001250050969
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine is related to albumin excretion rate in patients with diabetes mellitus: a new link between diabetic nephropathy and cardiovascular disease?

Abstract: The high risk of cardiovascular disease in patients with diabetes mellitus, particularly in those with nephropathy, is not completely explained by classical risk factors. A high plasma homocysteine concentration is an independent risk factor for cardiovascular disease but information on its association with diabetes is limited. Fasting homocysteine concentrations were measured in the plasma of 165 diabetic patients (75 with insulin-dependent [IDDM]; 90 with non-insulin-dependent diabetes [NIDDM]) and 56 non-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
4
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(125 citation statements)
references
References 46 publications
14
103
4
4
Order By: Relevance
“…We know that Hcy levels are higher in type 2 DM patients (30,31). In our study, we found Hcy levels even higher in the diabetic group than in the control group (respectively 12.3 ± 6.5 µmol/L and 10.8 ± 4.6 µmol/L ), but this difference had not statistical significance.…”
Section: Discussioncontrasting
confidence: 70%
“…We know that Hcy levels are higher in type 2 DM patients (30,31). In our study, we found Hcy levels even higher in the diabetic group than in the control group (respectively 12.3 ± 6.5 µmol/L and 10.8 ± 4.6 µmol/L ), but this difference had not statistical significance.…”
Section: Discussioncontrasting
confidence: 70%
“…Plasma Hcys concentrations are elevated in patients with diabetes (58,59), and a relationship between hyperhomocysteinemia and increased risk of cardiovascular morbidity and mortality has been established in patients with type 2 diabetes (6 -10). We previously demonstrated that Mo LPL, a proatherogenic protein, is increased in patients with type 2 diabetes (30) and that peripheral factors are, at least partly, responsible for this alteration (30 -32).…”
Section: Discussionmentioning
confidence: 99%
“…development of nephropathy, whereas diabetes mellitus per se most likely is not the cause of increased plasma homocysteine levels (24). HHcy may occur also in microalbuminuric patients with mild forms of renal dysfunction (7,17,25).…”
Section: Discussionmentioning
confidence: 99%
“…The study had previously been approved by an institutional ethics committee and all included subjects had approved their participation. A total of 8 4 subjects were included: 64 with diabetes mellitus type 2 (42 males/22 females) and with the presence of diabetic nephropathy (persistent urinary albumin excretion (UAE) >30 mg/24 h) (16,17), divided into two groups according to their fasting plasma tHcy levels [the first group with HHcy (the normal range in our laboratory was 5-12 mmol/L), and the second with NHcy], and 20 healthy controls (12 males/8 females).…”
Section: Methodsmentioning
confidence: 99%